2022 13th International Conference on Information, Intelligence, Systems &Amp; Applications (IISA) 2022
DOI: 10.1109/iisa56318.2022.9904362
|View full text |Cite
|
Sign up to set email alerts
|

The MiB System: An interactive storytelling experience in the wine industry

Abstract: The wine industry has evolved over time to tackle the emerging needs of both wine professionals and consumers. Especially during the last decades, there is a growing need for transparency and details to ensure consumers buy safe, healthy, and environmentally-friendly food products. These details include for example information about the winemaking process, farm practices, area description (i.e. geological), or the prevailing weather conditions throughout the year. However, this kind of information does not exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The survey showed that around 52% of New York residents and 68% of Paris residents are more sensitive to the environmentally-friendly approach. The survey also showed that the consumers in the 21-35 age group buy "responsible" wine on a regular basis (22% in New York and 35% in Paris) than the older generation (15% in New York and 30% in Paris) 5 .…”
Section: Natural and Organic Wine And Biodynamic Winementioning
confidence: 94%
See 1 more Smart Citation
“…The survey showed that around 52% of New York residents and 68% of Paris residents are more sensitive to the environmentally-friendly approach. The survey also showed that the consumers in the 21-35 age group buy "responsible" wine on a regular basis (22% in New York and 35% in Paris) than the older generation (15% in New York and 30% in Paris) 5 .…”
Section: Natural and Organic Wine And Biodynamic Winementioning
confidence: 94%
“…Transparent labeling is a strong trend in the wine industry 6 , aimed at providing consumers with more detailed information about the wine they are purchasing (Johnson, Thach, and Shweiger, 2013). This often includes information about the production process, composition, and growing practices (Chrysakis et al, 2022).…”
Section: Transparent Labelingmentioning
confidence: 99%
“…Our research expands the discourse on storytelling by illustrating its profound impact on consumer assessments, especially within the context of winery e-commerce. The strategic application of storytelling, from underdog tales that resonate with consumers on an emotional level (Delgado-Ballester, 2020) to innovative approaches such as the Message-in-a-Bottle project (Chrysakis et al , 2022) for dynamic content management, showcases the versatility of narratives in enhancing brand loyalty and encouraging positive consumer actions.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…This paper is an extension of the works [10,11] that presented earlier versions of the system. Here we describe in detail the deployed system and all of its aspects, including the sustainability and authenticity-related components and information.…”
Section: Introductionmentioning
confidence: 99%